Brazilian perspective: antimicrobial stewardship in solid organ transplant. Issue 5 (18th October 2022) - Porto, Ana Paula Matos; Tavares, Bruno de Melo; de Assis, Denise Brandão; Mendes, Elisa Teixeira; Girão, Evelyne Santana; Perdigão Neto, Lauro Vieira; Falcão, Maria Alice Pimentel; de Oliveira, Maura Salaroli; Freire, Maristela Pinheiro; Guimaraes, Thais; Arantes, Tiago; Levin, Anna Sara; et al.
Abstract: Background: The incidence of multidrug resistant organisms (MDROs) infections among solid organ transplant (SOT) patients is very high in Brazil. Methods: This review will discuss antimicrobial use and resistance in SOT in Brazil, highlighting the main barriers and facilitators for implementation of an antimicrobial stewardship programme (ASP). Results: The most common group of MDROs is carbapenem‐resistant Gram‐negative bacteria and vancomycin‐resistant Enterococcus. Carbapenem‐resistant Enterobacterales (CREs) are the most frequent MDROs and have been reported as donor‐derived as well. Although ASPs are mandatory in the country, there is a lack of information regarding ASPs in SOT recipients. The main barriers for the implementation of ASPs in Brazilian hospitals are lack of electronic medical records, absence of national guidelines specific to SOT recipients, lack of recommendations on surveillance culture to evaluate colonization and transmission of donor‐derived MDROs, limited availability of rapid diagnostic tests, and insufficient pharmacist and clinician time allocated to ASP activities in some SOT centers. Conclusions: The incidence of MDRO infections caused mainly by VREs and CREs is very high in the country. There is limited data regarding antimicrobial use among SOT recipients in Brazil. The absence of antimicrobial stewardship national guidelines specific to SOT recipients is one of the main barriers for the implementation of ASPs in Brazilian hospitals. Abstract :